2019
DOI: 10.3390/agronomy9020051
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Ascorbic Acid Content and Salinity Tolerance of Cherry Tomato Plants by Suppressed Expression of the Ascorbate Oxidase Gene

Abstract: eg (M.I.A.M.) 2 INRA, UR1052, Génétique et amélioration des fruits et légumes, DomaineAbstract: Ascorbic acid is considered to be one of the most important antioxidants in plants and plays a vital role in the adaptation of plants to unfavorable conditions. In the present study, an ascorbate oxidase gene (Solyc04g054690) was over-expressed in cherry tomato cv. West Virginia 106 lines and compared with previously studied RNAi silenced ascorbate oxidase lines. Two lines with lower ascorbate oxidase activity (AO−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 40 publications
8
42
0
Order By: Relevance
“…The presence of NaCl salt in the plant growing medium inhibited the growth of both aerial part and roots of the young plants of all the 7 cultivars. The reduction of plant growth by salt stress is a current phenomenon as reported in several vegetables species including tossa jute (Ghosh et al, 2013;Ben Yakoub et al, 2019), amaranth amaranth (Omami et al, 2005;; pepper (Sikha et al, 2013;R'him et al, 2013): tomato (Abir et al, 2006;Albacete et al, 2008;Ould Mohamdi et al, 2011;Abdelgawad et al, 2019 ; Our results revealed variability among the response of the 7 cultivars to salt stress according to the growth parameter.…”
Section: Effects Of Salt Stress On Plant Growthsupporting
confidence: 59%
“…The presence of NaCl salt in the plant growing medium inhibited the growth of both aerial part and roots of the young plants of all the 7 cultivars. The reduction of plant growth by salt stress is a current phenomenon as reported in several vegetables species including tossa jute (Ghosh et al, 2013;Ben Yakoub et al, 2019), amaranth amaranth (Omami et al, 2005;; pepper (Sikha et al, 2013;R'him et al, 2013): tomato (Abir et al, 2006;Albacete et al, 2008;Ould Mohamdi et al, 2011;Abdelgawad et al, 2019 ; Our results revealed variability among the response of the 7 cultivars to salt stress according to the growth parameter.…”
Section: Effects Of Salt Stress On Plant Growthsupporting
confidence: 59%
“…The enhancement of vitamin C in silenced MDHAR lines could be due to a decrease in degradation [44]. In cherry tomato, the suppression of AOX was also found to increase vitamin C, lycopene, and carotene contents of the fruits and to confer tolerance to salt stress [222].…”
Section: Vitamin C Biofortificationmentioning
confidence: 99%
“…An ascorbate peroxidase was overexpressed in all genotypes, although its activation may be multifactorial. For fieldgrown tomato, the relation between AO and AsA content in mature fruits is complex, because transgenic lines with either higher or lower AO activity had higher AsA amount than control lines [50]. In pepper, in addition of a positive correlation between AO activity and AsA level [51], the role of the AO gene has been connected with the regulation of cell division and growth in expanding tissues [52].…”
Section: Discussionmentioning
confidence: 99%